Intellectual capital performance of financial institutions in Malaysia - Ting I.W.K.; Lean H.H. (2023)
Purpose: This paper aims to examine the intellectual capital performance and its relationship with financial performance of financial institutions in Malaysia for the period 1999 to 2007. Design/methodology/approach: The value added intellectual coefficient (VAIC) by Pulic is used. Findings: The paper reveals that VAIC and ROA are positively related among Malaysia's finance sector. The results also show that the three components of VAIC are associated with profitability with the explanatory power of 71.6 per cent. Research limitations/implications: This study does not cover all finance companies in Malaysia due to limited data. Future study should therefore further improve on the aspect of coverage. Practical implications: The findings may serve as a useful input for bankers to apply knowledge management in their institutions. Furthermore, the financial institutions may have more definite understanding of the composition of intellectual capital and evaluate its developing tendency periodically. Originality/value: This is the first paper that examines the relationship of VAIC and firm's profitability for companies listed in the Bursa Malaysia finance sector. Emerald Group Publishing Limited.